(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
12 species of macroscopic ascomycetes from Pezizales in Nоrthen part оf the Black Sea region were revealed. Among them 6 species were mycorrhizal fungi, 5 humicolour saprotrophes and 1 – xylotroph. Among found species of fungi Helvella ephippium, Peziza ampliata and Trichophaea gregaria are new for the steppe region of Ukraine. Helvella ephippium is rare in Ukraine. Description, illustration of microstructures and general distribution were given for it.